PENGARUH AUDIT FEE, FINANCIAL DISTRESS DAN REPUTASI REPUTASI KANTOR AKUNTAN PUBLIK (KAP) TERHADAP AUDIT DELAY - Sonia Dewi; Julian Maradina (Jurnal Nusa Akuntansi, 2026)
This research aims to determine and obtain empirical evidence regarding the influence of Audit Fees, Financial Distress, and KAP Reputation on Audit Delay in food and beverage sector companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2023. This type of research is quantitative and uses secondary data in the form of annual reports or audited financial statements sourced from the official website of the Indonesia Stock Exchange (BEI) and company websites. The population in this study consists of food and beverage sector companies listed on the BEI during 2019-2023, totaling 80 companies as the population, and the sampling technique used is purposive sampling, fulfilling the criteria of 21 companies selected as the sample over 5 (five) years of observation. The data analysis technique in this study uses panel data regression analysis in Eviews 13 software. The results of this study indicate simultaneously that Audit Fee, Financial Distress, and KAP Reputation have an effect on Audit Delay. Partially, it shows that Financial Distress affects Audit Delay, whereas Audit Fee and KAP Reputation do not affect Audit Delay. Keywords: Audit Delay; Audit Fee; Financial Distress; KAP Reputation.